Sistem Pakar Diagnosa Penyakit Infeksi Saluran Pernapasan Akut Menggunakan Metode Forward Chaning - Andriyanto Andriyanto; M.Ifran Sanni; Dody Dody (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
Health is something very important and valuable, without a healthy one can not enjoy life. As the times progressed, the types of disease increased with new or even different manifestations of previous symptoms. Medical diagnosis (abbreviated DS or Dx) is the process of determining a disease or condition of symptoms and signs of a person. ARI disease is one type of disease that suffered someone. ARI is an inflammatory process in the area of the respiratory system starting from the top of the nasal cavity, progressing to the pharynx and larynx. ARD disease without good knowledge can lead to erroneous treatment of a disease, may be more severe or even cause death if late helped. One tool that is very helpful in making diagnosis of internal diseases is expert system. Expert system in general is a system that seeks to adopt human computer knowledge, so that the computer can solve problems as is usually done by experts. Hopefully with this system, the layman can solve certain problems either slightly complicated or complicated though without the help of experts in the field As for experts, this system can be used as an experienced assistant. Application of expert system used to diagnose internal diseases by using Forward Chaning method where the diagnosis is done by analyzing the input of symptoms in the form of questions about what is felt by the patient. Input the symptoms are then processed by using certain rules in accordance with the science of experts or general practitioners who previously been stored in the rules of treatment. Analysis results then checked compatibility with the doctor's diagnosis to know the truth. Keywords: Expert System, Diagnosis, ARI, Forward Chaining